Avoiding the 'Thucydides trap' : U.S.-China relations in strategic domains - Wang, Dong, 1977-; Tanner, Travis (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"As the relationship between China and the United States becomes increasingly complex and interdependent, leaders in Beijing and Washington are struggling to establish a solid common foundation on which to expand and deepen bilateral relations. In order to examine the challenges facing US-China relations, the National Bureau of Asian Research (NBR) and the Institute for China-US People-to-People Exchange of Peking University brought together a group of leading experts from China and the United States in Beijing and Honolulu to develop a conceptual foundation for US-China relations into the future, tackling the issues in innovative ways under the banner of US-China Relations in Strategic Domains. The resulting essays assess US-China relations in the maritime and nuclear sectors as well as cyberspace, space and via the lens of P2P and Mil to Mil exchanges. Scholars and students in political science and international relations are this presented with a diagnosis and prognosis of the relations between the two superpowers"--
Introduction / Travis Tanner and Wang Dong -- U.S.-China Relations in the Maritime Security Domain / Christopher Yung and Wang Dong -- Seeking Strategic Stability for U.S.-China Relations in the Nuclear Domain / Elbridge A. Colby and Wu Riqiang -- Reducing and Managing U.S.-China Conflict in Cyberspace / Adam Segal and Tang Lan -- U.S.-China Strategic Relations in Space / Brian Weeden and Xiao He -- Stepping Up Investments in U.S.-China Relations: Making People-to-People Exchange a Strategic Priority / Travis Tanner and Zhao Minghao -- Sino-U.S. Military-to-Military Relations / Roy D. Kamphausen with Jessica Drun -- Sino-US Military Relations: Interests, Challenges and Solutions / Xu Hui with Yu Ying -- Conclusion / Tiffany Ma.
OCLC-licensed vendor bibliographic record.
Keywords: United States -- Foreign relations -- China; China -- Foreign relations -- United States